2008
DOI: 10.1159/000156479
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Neuropsychological Functioning during Alcohol Detoxification

Abstract: This study investigates changes in neuropsychological functioning during early abstinence from alcohol. 30 alcohol-dependent inpatients were tested at intake (day 4 of admission) and post detoxification (day 26), using a test-retest design. The neuropsychological battery included measures of pre-morbid IQ, full-scale IQ, verbal and non-verbal measures of memory and executive function. IQ was within the normal range at intake and comparable with age-adjusted normative values and there were some impairments in m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
54
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(59 citation statements)
references
References 69 publications
4
54
1
Order By: Relevance
“…In an inpatient study, Manning and colleagues also found that 4 weeks after detoxification, alcoholic patients had significant increases in performance scores of working memory, verbal fluency, and verbal inhibition. 26 Although the topiramate doses given in this study (a mean of 253.1 mg/day) were relatively lower than those administered in some studies, they are the doses commonly used for the treatment of alcoholism. Two previous studies of topiramate-induced cognitive impairment applied this agent at higher doses in adults with partial seizure (mean dose of 414 mg/day) 22 and in healthy volunteers (330 mg/ day).…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…In an inpatient study, Manning and colleagues also found that 4 weeks after detoxification, alcoholic patients had significant increases in performance scores of working memory, verbal fluency, and verbal inhibition. 26 Although the topiramate doses given in this study (a mean of 253.1 mg/day) were relatively lower than those administered in some studies, they are the doses commonly used for the treatment of alcoholism. Two previous studies of topiramate-induced cognitive impairment applied this agent at higher doses in adults with partial seizure (mean dose of 414 mg/day) 22 and in healthy volunteers (330 mg/ day).…”
Section: Discussionmentioning
confidence: 61%
“…The improvement of language and delayed recall in this sample appears to be in concordance with previous findings. In an inpatient study, Manning and colleagues also found that 4 weeks after detoxification, alcoholic patients had significant increases in performance scores of working memory, verbal fluency, and verbal inhibition 26 …”
Section: Discussionmentioning
confidence: 96%
“…Limited longitudinal designs have also compared the same alcohol dependent sample tested twice: at some point very early in treatment after detoxification, and again later in treatment or soon after the end of treatment. These studies have suggested that whereas some cognitive recovery, such as verbal learning, is observable early after detoxification, recovery in executive and memory domains is slower, occurring over one year and longer (Sullivan et al 2000; Goldman 1990; Parsons 1998; Bates et al 2002a; Bates et al 2005; Manning et al 2008; Bates et al 2004; Dingwall et al 2011; Rosenbloom et al 2004; Rosenbloom et al 2007). When considered collectively, as in a recent meta-analysis (Stavro et al 2012) and review (Fernandez-Serrano et al 2011), these studies paint a picture of substantial cognitive recovery in the short term (one month), with more modest increases across mid-term (up to one year), and long-term in multiple cognitive domains.…”
Section: Cognitive Recovery In Audmentioning
confidence: 99%
“…Many studies have used parts of standardized IQ tests [19, 22, 35-38], thus providing results that might not reflect global intellectual functioning but rather an area or domain of intellectual functioning. The timing of IQ testing has varied greatly among previous studies, with some only requiring abstinence on the day of testing [27, 39] or within the first days after admission [38].…”
Section: Introductionmentioning
confidence: 99%